Health care delivery model in India with relevance to diabetes care. Issue 10 (October 2022) - Das, Ashok Kumar; Saboo, Banshi; Maheshwari, Anuj; Nair V, Mohanan; Banerjee, Samar; C, Jayakumar; V, Benny P.; Prasobh P, Sunil; Mohan, Anjana Ranjit; Potty, Vasudevan Sambu; Kesavadev, Jothydev
Abstract: The Indian healthcare scenario presents a spectrum of contrasting landscapes. Socioeconomic factors, problems with medical infrastructure, insufficiency in the supply of medical requisites, economic disparities due to major differences in diabetes care delivery in the government and private sectors and difficulty in accessing quality health care facilities challenges effective diabetes care in India. The article gives insights into the practical solutions and the proposed White paper model to resolve major challenges faced by the Indian diabetes care sector for effective diabetes care delivered at Jothydev's Diabetes Educational Forum Global Diabetes Convention 2019. Highlights: The prevalence of diabetes in India is on its rise. Socioeconomic factors, lack of diagnosis etc challenges Indian diabetes care system. Health care models appropriate for Indian scenario should be developed. Public-Private partnership is required for effective health care delivery. Abstract : Diabetes; Health care model; Patient adherence; India; Health care policies.